Subarachnoid Anesthesia in Young Patients: A Comparative Analysis of Two Needle Bevels. Issue 6 (1st November 1999) - De Andrés, Jose; Valia, Juan Carlos; Errando, Carlos; Rico, Gabriel; Lopez-Alarcon, Maria Dolores
Abstract : Background and Objectives: This prospective, randomized, double-blind study compares the efficacy of two spinal needles in terms of their performance characteristics and associated perioperative complaints in young patients. Methods: ASA I and II patients aged from 20 to 40 years undergoing lower limb orthopedic surgery were included during a 12-month period. After application of the protocol, 158 patients were recruited. The patients were randomized to two groups: group I: 26-gauge Atraucan (n = 79) and Group II: 27-gauge Whitacre (n = 79). A study was made of the demographic parameters, technical characteristics, and peri- and postoperative complications. Results: No significant differences were found in the technical handling of the needles, number of attempts made to achieve the puncture, or the time required to perform the technique. No technical failures (spinal anesthesia inadequate for the planned surgery) were reported, and the frequency of complications during the procedure was identical in both groups. Frequency of postdural puncture headache (3.8%) or severity and duration showed no difference between the two groups. The overall assessment of postoperative complications revealed similar scores for both needles. Conclusions: Technical handling (ease with which block was performed) of the needles analyzed was extremely easy, showing a high success rate which associated with the similar incidence of complications. Type of bevel does not appear to be a determining factor in the quality or morbidity associated with subarachnoid block when fine-gauge needles are used in young patients.